Evaluasi Kinerja Jalur Pedestrian di Kawasan Ruang Terbuka Hijau Publik Perkotaan - Nahdatunnisa Nahdatunnisa; Henny Pratiwi Adi; Slamet Imam Wahyudi; M. Arzal Tahir (Prosiding ESEC, 2022)
This study aims to evaluate the performance and to determine the pedestrian path satisfaction index inthe public green open space area of Kendar Cuty by using 29 variables which are a combination of quantitative and qualitative research, with a total sample of 399 respondents. This study uses the Importance Performance Analysisi (IPA) analysis method in assessing the performance of the existing pedestrian path, and the Customer Satisfaction Index (CSI) to performance the user satisfaction index for the services received. The results obtained in this study are related to the performance of the existing pedestrian path wich consists of good categories : facilities for pedestrians with special needs (guiding blocks), availability of road markings, available crossing paths, security systems (cctv, security posts), speed control facilities, cleanliness level. Adequate/ordinary categories : dimensions of pedestrians paths, lighting of pedestrian paths, differences inthe level of heigth of pedestrian path with road bodies, availability of pedestrian path markings and signs/sigals, surface texture of trash bins. ba/bad categories : the availability of ramps, pedestrian paths connected to urban transportation element, continuity of pedestrian paths, obstructions in pedestrian paths, crossing, and noise suppression facilities, while the pedestrian path user satisfaction index for services is only in the category quite satisfied with a value of 65.57%.